Melacak Sinisme Al-Zamakhsyari Terhadap Perempuan (Aplikasi Semiotika-Psikoanalisis Jacques Lacan) - Alfan Shidqon; Zakiyan Rifqa; Noufal P. Tumewu (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2023)
This article will review the bias of al-Zamakhshari, a lifelong single mufasir, when interpreting Qur'anic verses concerning women. To what extent does his singleness trigger a negative view of women. This research departs from the perspective of Lacanian semiotics-psychoanalysis that human desires have a strong influence on their views on things and this can be observed through the language they produce. There are two issues to be answered: first, what is the desire behind al-Zamakhshari's slovenliness; second, how does it relate to the interpretation of verses about women. Based on a literature review of al-Zamakhshari's historical literature and his tafseer al-Kasysyaf, this study finds that al-Zamakhshari's desire for singleness is covered by various factors; ranging from religious priorities, patriarchal environment, to personal trauma. Indications of cynicism in his interpretation then lead to the glorification of the negative side of women, male superiority, and resistance to the concept of living in pairs as absolute human nature. However, the cynicism is not radical because in many interpretations of verses about women, al-Zamakhshari presents a legal-normative review so that it appears proportional.